EVALUASI PENGKAYAAN MINYAK DAUN KELOR PADA Artemia sp. TERHADAP PERTUMBUHAN DAN PERKEMBANGAN LARVA IKAN MAS SINYONYA - Tansya Anggraeni; Saifullah; Lukman Anugrah Agung (Journal Publicuho, 2025)
This study aimed to evaluate the effect of Moringa oleifera leaf oil enrichment on Artemia sp. as live feed toward the growth and survival rate of goldfish larvae (Cyprinus carpio L.). The experiment was conducted at the Aquaculture Laboratory, University of Sultan Ageng Tirtayasa, from July to August 2024. A completely randomised design (CRD) was used with four treatments and three replications: P0 (without enrichment), P1 (0.1 mL/L), P2 (0.2 mL/L), and P3 (0.3 mL/L). Observed parameters included absolute length and weight gain, daily growth rate (LPPH), specific growth rate (SGR), survival rate (SR), and proximate composition of Artemia sp. and fish larvae. The results showed that enrichment with Moringa leaf oil significantly affected (p<0.05) the growth and nutrient content but did not significantly affect the survival rate of the larvae. The best results were obtained at the 0.3 mL/L dose (P3) with an absolute length of 2.04 cm, absolute weight of 0.345 g, daily growth rate of 10.16%, and specific growth rate of 0.017%. The protein and fat contents of Artemia sp. increased to 12.68% and 2.50%, respectively. Water quality during the study remained within the optimal range for goldfish larval rearing. In conclusion, Artemia sp. enriched with Moringa oleifera leaf oil at a concentration of 0.3 mL/L is recommended to enhance the growth performance of goldfish larvae.